2011
DOI: 10.2500/ajra.2011.25.3682
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Differentially Expressed microRNAs in Allergic Rhinitis

Abstract: The report indicated that many miRNA expressions were altered in AR and differentially expressed miRNAs appear to be involved in the development of AR. The study of miRNAs may lead to a better understanding about the roles of identified miRNAs in the pathogenesis of AR; this would be considered in future therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 25 publications
2
71
0
Order By: Relevance
“…In this study, miRNAs involved in dermal TDI sensitization were identified using a murine model. A role for miRNAs in airway inflammatory disorders including asthma and allergic rhinitis has recently been described in both human and animal models (Ariel & Upadhyay, 2012;Garbacki et al, 2011;Shaoqing et al, 2011). It has been proposed that the specific mechanism of miRNA action involves a large number of miRNA targeting multiple functionally-related mRNA to orchestrate a co-ordinated regulation of multiple steps in the pathogenesis of asthma, but these processes are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, miRNAs involved in dermal TDI sensitization were identified using a murine model. A role for miRNAs in airway inflammatory disorders including asthma and allergic rhinitis has recently been described in both human and animal models (Ariel & Upadhyay, 2012;Garbacki et al, 2011;Shaoqing et al, 2011). It has been proposed that the specific mechanism of miRNA action involves a large number of miRNA targeting multiple functionally-related mRNA to orchestrate a co-ordinated regulation of multiple steps in the pathogenesis of asthma, but these processes are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-142-3p enhances Fc⑀RI-mediated degranulation, and miR-142-3p rescues the reduction of degranulation by silencing Dicer (18). Many miRNA expressions were altered in allergic rhinitis, and differentially expressed miRNAs appear to be involved in the development of allergic rhinitis (19). miR-155 regulates allergic asthma by modulating TH2 response through the transcription factor PU.1 (20).…”
mentioning
confidence: 99%
“…Furthermore, it was observed that miR-let-7e overexpression activated the JAK1/STAT3 signaling pathway. Previous studies have suggested the role of miRNAs in controlling allergic airway inflammation (10,11). The miR-let-7 family of miRNAs is highly conserved across animal species, serving important roles in the regulation of cell proliferation and differentiation (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miRNAs regulate the activity of immune cells within the innate and adaptive immune systems (8,9), and their aberrant expression may result in immune disorders. Previous studies have emphasized the important role of miRNAs in controlling allergic airway inflammation (10,11). Furthermore, Teng et al (12) observed that that miRNA-143 involved in the pathologic process of AR, which was significantly down-regulated in nasal mucosal tissues of AR patients compared with healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%